Analisis Perbandingan Bahan Bakar Gas dan Energi Listrik Dari Biogas Dengan Memanfaatkan Feses Manusia - Utama, Nanda; Jelita, Marhama (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The increasing population growth every year results in many problems, the problem that arises is the increasing amount of waste in the form of human feces that is thrown into septic tanks. Large amounts of human feces can be found, such as in Islamic boarding schools with the number of students continuing to increase, causing the amount of feces to also continue to increase. The problem of human feces can be overcome by utilizing feces into biogas. Utilizing biogas is a solution to replace fossil fuels and also prevents human waste from polluting the environment. The aim of the research is to find out the potential amount of student feces, find out the biogas produced using the anaerobic method, find out the results of converting biogas to LPG fuel and electrical energy and compare the costs of the energy conversion process so as to save the operational costs of the Islamic boarding school. The amount of feces produced from 59 people was 14.75 kg/day with the biogas obtained being 0.068 m3/day, the conversion of biogas to LPG fuel as much as 0.03128 kg/day, the electrical energy produced was 223,892 kJ/day, the result of converting biogas to electrical energy is 0.06224 kWh/day, the cost of saving gas fuel is IDR. 33,456 and the cost of saving electrical energy is Rp. 2,524. So the result of using biogas from human feces is that the greatest energy obtained is electrical energy, while the greatest savings are gas fuel.Keywords - Human Feces, Gas Fuel, Electrical Energy, Biogas, Anaerobic Methods.